Economic Aspects of Rural Tourism - Bainé Szabó, Bernadett (Acta Agraria Debreceniensis, 2003)
necessary to ensure the livelihoods of those leaving the agricultural sector and to supplement the incomes of those working in agriculture. I research rural development in four settlements in Hajdú-Bihar County, in Balmazújváros, Hortobágy, Tiszacsege and Egyek, all bordering Hortobágy National Park.There are many alternative income sources in settlements in the Hortobágy area, such as organic farming, production herbs, hungaricums, small animals and arts and crafts, as well as rural tourism. Rural tourism is not for subsistence, but a supplementary income source, mainly available during the summer time. I made a survey of rural hosts in the four examined settlements, and according to my results, I constructed a model reflecting the cost-benefit relation, as well as the payment period conditions of rural tourism. I am going to show whether it is worth dealing with rural tourism, and if yes, under what conditions. Rural tourism contributes to the maintenance of rural modes of living, in this way it has significant cultural, economic, ecological and social aspects, as well. It is crucial for settlements to create the appropriate conditions needed for joining rural tourism, if it is worth joining at all, and to realise investments for all these. Rural tourism has strict requirements for the levels of environment, infrastructure and services. Studying the Western-European practices, Hungary is lagged behind in the conditions of rural tourism and rural hosts have done their activities mainly out of necessity and not to maintain traditions. Rural tourism may result in success only by co-operation and over the long-run.